From Model to Bedside: What Kind of OSA Risk Prediction Tools Do We Need More Of? [Response to Letter] - Guo B (Nature and Science of Sleep)
Botang Guo Department of General Practice, The Affiliated Luohu Hospital of Shenzhen University Medical School, Shenzhen, 518001, People’s Republic of ChinaCorrespondence: Botang Guo, Email hmugbt@hrbmu.edu.cn